The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1589/jpts.15.65
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Continuous Ultrasound and Pulsed Ultrasound on Soft Tissue Injury Markers in the Rat

Abstract: Abstract. The cellular effects of pulsed and continuous ultrasound on the protein content of muscle after trauma were determined in this study. Rats were subjected to a single impact trauma to the gastrocnemius. Six major treatment groups were employed: (1) uninjured control, (2) injured control, (3) & (4) uninjured ultrasound treated, and (5) & (6) injured ultrasound treated. The ultrasound treated groups were subdivided into continuous ultrasound, and pulsed ultrasound treatments (dosage = 1.0 watts/cm 2 × 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…[17][18][19][20][21][22] LIUST has been shown to modify cellular and humoral signaling factors, especially the bioavailability of nitrous oxide, thereby regulating interstitial permeability and tissue fluid balance; 9,12,13,29 this in turn results in decongestion of the nasopharyngeal mucosa, regression of interstitial edema and of nasal obstruction/congestion in patients with chronic rhinosinusitis. Supporting this assumption, recent reports in the literature have shown strong correlations among nasal mucosa congestion rates, fibrosis, and vascular density in patients with chronic rhinosinusitis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[17][18][19][20][21][22] LIUST has been shown to modify cellular and humoral signaling factors, especially the bioavailability of nitrous oxide, thereby regulating interstitial permeability and tissue fluid balance; 9,12,13,29 this in turn results in decongestion of the nasopharyngeal mucosa, regression of interstitial edema and of nasal obstruction/congestion in patients with chronic rhinosinusitis. Supporting this assumption, recent reports in the literature have shown strong correlations among nasal mucosa congestion rates, fibrosis, and vascular density in patients with chronic rhinosinusitis.…”
Section: Discussionmentioning
confidence: 99%
“…Pulsed ultrasound waves act on a cell and/or molecular level by altering membrane permeability, ionic concentration gradients and cell biochemical activity. [14][15][16][17] More recently, ultrasound has been employed as adjuvant therapy in several conditions such as tissue repair, 16 reduction of muscle and joint pain, 17,18 modulation of inflammation, 19,[20][21][22] and reduction of tendon adhesions. [17][18][19] A few studies have demonstrated that LIUST-induced accelerated skin tissue repair results from local modulation of cell mediators/signalers such as nitric oxide, histamine and other cytokines that are involved in inflammation in healing; it also increases the number of fibroblasts and collagen synthesis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there are few studies that demonstrate that therapeutic ultrasound assists in wound healing. Therapeutic ultrasound may be classified as continuous (thermal) or pulsed (nonthermal) [4], and it has been claimed to promote tissue repair, specifically by enhancing cell proliferation and protein synthesis during the healing of skin wounds [5], tendon injuries [6,7], and fractures [8,9].…”
Section: Introductionmentioning
confidence: 99%